MANAJEMEN STRATEGI DALAM MENINGKATKAN MUTU LULUSAN DI SEKOLAH MENENGAH ATAS ISLAM TERPADU NURUL ILMI KOTA JAMBI - Fahmin, Nursyahrani; Mahmud, Mahmud; Jannah, Siti Raudhatul (Universitas Yudharta Pasuruan, 2024)
This research aims to describe strategies for improving the quality of graduates through the roles and duties of school principals and assisted by deputy principals in managing the strategic management process which is carried out starting from environmental observation, strategy formulation, strategy implementation to the evaluation stage. This research is qualitative research with a qualitative descriptive approach. Data collection techniques were carried out using observation, interviews and documentation methods. The findings of this research include, first, the strategic management process carried out in improving the quality of graduates, namely through the analysis stage (internal and external environmental analysis), strategy formulation is carried out by an appointed team, after that the formulation stage is carried out. followed by the implementation stage, and as follows: Lastly is evaluation which includes supervision, providing reports on programs that have been implemented, and organizing meeting agendas. Furthermore, how important it is for this management strategy to be improved in order to produce quality graduates, so as to expand future opportunities and minimize possible risks. Then there are factors that influence the process of improving the quality of graduates, namely in terms of teacher quality, outstanding students, and of course the availability of complete facilities. And the obstacle experienced is the lack of student motivation. Therefore, teachers need to foster students' learning motivation. Teachers as drivers of learning must try to make their students more enthusiastic about learning